A comprehensive review on Crossflow turbine for hydropower applications. (15th November 2021) - Anand, R.S.; Jawahar, C.P.; Bellos, Evangelos; Malmquist, Anders
Abstract: A Crossflow turbine is a device used to generate power from hydro, which is a renewable source of energy. The salient feature of this turbine is its simplicity in construction. In the past few decades, variables such as flow diverter, air holes, bidirectional flow were introduced in the turbine design to improve its efficiency. This paper presents a comprehensive review of the performance of the cross flow turbine. The review of literature is classified into experimental and numerical studies. The present study highlights the optimum range of geometrical variables required for the efficient design of a cross flow turbine. The study also emphasizes the importance of employing the cross flow turbine in remote places where run-of-river hydro power plants are feasible, as it provides a low-cost energy solution. The outcome of the present study will help the researchers to identify the research gap based on the present status of work done and to improve the performance of the cross flow turbine further in the future. Highlights: Experimental investigations on the performance of cross flow turbine is reviewed. Numerical investigations carried out by several researchers is presented. Performance of the cross flow turbine with varying geometrical parameters is analyzed. Research gap and the scope for future work are discussed.